Pengaruh Dukungan Orang Tua, Dan Fasilitas Belajar Di Sekolah Terhadap Hasil Belajar dengan Kesiapan Belajar sebagai Variabel Mediasi (Pada Pembelajaran Pratikum Akuntansi Jasa, Dagang Dan Manufaktur Akuntansi Siswa Kelas XI Program Keahlian Akuntansi D - Nanda Asmar Hariati; Armida S (Jurnal Salingka Nagari, 2023)
The goal is to decide on impact supporting parents and improving school facilities for learning proces readiness and accounting learning outcomes for Cersa Pasaman Vocational School class XI students enrolled in the accounting expertise program in service, trade, and manufacturing accounting practicum learning. SPSS 26 was used to perform route analysis. (1) Parents' support influences learning readiness, according to the findings of this study. (2) Learning facilities have an impact on learning readiness. (3). Parental support has an impact on learning outcomes. (4) Learning facilities in schools have an impact on learning results. (5). Learning preparedness has an impact on learning outcomes. (6). The Accounting Expertise Program at SMK Cersa Pasaman class XI students' learning preparedness and learning results are influenced by parental support and learning facilities.